Translation and validation of the Greek version of the Jefferson Scale of Attitudes toward Physician and Nurse Collaboration (JSAPNC) - Malliarou, Maria; Domeyer, Philippe J.; Bamidis, Panagiotis D.; Sarafis, Pavlos (My University, 2021)
The Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration (JSATPNC) is an established tool to assess attitudes toward physician-nurse collaboration. The aim of this study was to translate and culturally adapt the JSATPNC for use in Greece and test its psychometric properties. The final study sample included 621 physicians and nurses working in two general hospitals of Northern Greece during 2017. The study sample was randomly split into two halves; separate exploratory and confirmatory factor analyses were conducted. A regression analysis including sociodemographic variables was performed to predict the JSATPNC total score. The Cronbach’s alpha was .74. A four-scale model (a) interprofessional collaboration, (b) involvement in decision-making, (c) expertise, (d) physician’s dominance was extracted from the exploratory factor analysis. The confirmatory factor analysis indicated an acceptable model fit (RMSEA = .069, SRMR = .083, TLI = .875, CFI = .903). There was adequate evidence for both convergent and discriminant validity, apart from the “physician’s dominance” scale; the exclusion of items 9 and 12 from this scale resulted in an alternative model with the improved model fit (RMSEA = .062, SRMR = .078, TLI = .902, CFI = .916). The test–retest intraclass correlation coefficients were all above .7. Age and profession of the respondents emerged as important predictors of the total scale score. The Greek version of the JSATPNC shows promise as a reliable and valid instrument for evaluating collaboration between physicians and nurses.
Keywords: Interprofessional collaboration; Communication; Teamwork; Validation; Greece; Psychometrics; JSAPNC